Desinformación tras el 11-S - Paniagua, Pedro (Estudios sobre el Mensaje Periodístico, 2002)
The communication campaigns that the American government has developed after September 11th with the objective of disseminate true and false information abroad has been stopped by to unwanted but predictable effects: the absence of credibility of that communication and the inability to keep the American media away from the disinformation. Anyway, the atmosphere founded in the media of the USA and Europe has favoured this communication campaigns.